القيود الواردة على ملكية العقار في الفقه الاباضي والتشريع الحديث في سلطنة عمان (دراسة مقارنة) - Mahmood Khalifa Ghalib Al-Rashdi
This study aims at outlining the constraints (al-quyud) on realty ownership in the Ibadhi jurisprudence, and the modem Omani legislation, in acknowledgment of the importance of these constraints to the public life, and the judicial authority. The researcher addressed the realty-related constraints from an Islamic juristic perspective, with focus on the Ibadhi jurisprudence embraced in the Sultanate of Oman. The study started with a historical overview of the Ibadhi jurisprudence, highlighting the relatively short Omani experience with its current modem legal system. The researcher then discussed ownership and real estate &before offering a compilation of the juristic texts relevant to the study's topic, with special emphasis on the conceptual development of constraints in the Sultanate and their implications. The collation included the lawful means of realty ownership6 including seizure (al-hiyazah); neighbourhood preemption (right of way) (Al-shufah); Sale-and-Purchase; legacy; gift; and bequest. It also highlighted the constraints which impinge on the owner's authority over- and limit his usufruct- of his possessions, from the vantage points of the Ibadhi jurisprudence and the Omani modem laws. The study was essentially comparative, as it compared between the constraints stipulated by the old (Ibadhi) and modem Omani systems, with some Omani court verdicts for elucidation. The researcher adopted a variety of methods to build his arguments. The inductive method was used to generate the Islamic juristic views from the perspective of the Ibadhi jurists, as well as the modern legal texts in Oman. The analytical method was also adopted in the examination of the various juristic and legal texts, in addition to the comparative approach which was useful in telling the juristic and legal views apart. The study found that jurists have largely imposed constraints on real estate ownership, some of which were for the public interest6 and others for the protection of neighbours. People are6 for example6 barred from using their properties in a way that is abusive to the community or the neighbours. The study6 thus& confirms the benevolent character of the Islamic jurisprudence in its quest for balance between the social and individual rights. The study also highlighted the full harmony between the Islamic jurisprudence and the laws derived from it6 which makes the application Islamic teachings in modem legal systems completely adequate. The study concluded by a number of recommendations relevant to its findings.